Exploration of the main effective constituent and the mechanism in Astragali Radix in the treatment for doxorubicin-induced nephropathy by integrating metabolomics and molecular docking. (6th April 2023) - Li, Aiping; Cui, Wenbo; Zhao, Yirui; Luo, Tingting; Zhang, Qingyu; Liu, Yuetao; Li, Ke; Qin, Xuemei; Zhang, Lichao
Abstract: Ethnopharmacological relevance: Astragali Radix (AR) is the dried root of Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao or A. membranaceus (Fisch.) Bge. AR was the main medicine in a Chinese traditional prescription called Fangji Huangqi Decoction, and it has been used to treating nephrotic syndrome (NS) for thousands of years in China. In recent years, AR has been evidenced to have anti-inflammatory activity, antihyperglycemic activity, antioxidant activity, etc. There are two mainstream commodities for ARs in the market including the imitation wild AR and transplanted AR. However, it is not clear whether the imitation wild AR or transplanted AR and which kind of component, astragalus saponin, astragalus flavonoid or astragalus polysaccharide, makes a bigger contribution in treating NS. And the exact molecular mechanism is not fully understood. Aim of the study: To explore which kind of AR and which kind of component in AR makes the bigger contribution in treating NS, and exploring the molecular mechanism. Materials and methods: Firstly, HPLC-UV/ELSD was used for quantitative determination of the constituents in different ARs. Secondly, the efficacy of different ARs treating doxorubicin-induced nephropathy (DN) was compared by metabolomics. Thirdly, the protective effects of different constituents from ARs on the damage of MPC5 cells induced by adriamycin are validated. Finally, the effective constituents and mechanism of ARs against doxorubicin-induced nephropathy were investigated by network pharmacology and molecular docking. Results: Quantitative determination experiment and pharmacological experiment indicated that the AR produced from Gansu province (China) (transplanted AR) with a higher proportion of total saponins, has better efficacy in the treatment for DN. And the cell experiment validated the result that astragalus saponins has the better efficacy in protecting the podocyte against injury than astragalus flavonoids and polysaccharides. The network pharmacology and molecular docking study indicated that astragalus saponins were the main constituent of AR in the treatment for DN. The mechanism may involve in GnRH signaling pathway, VEGF signaling pathway and metabolic pathways, especially of bilirubin metabolism. Conclusions: Transplanted AR has better efficacy in the treatment for NS than imitation wild AR, astragalus saponins have better efficacy in the treatment for NS than astragalus flavonoids and polysaccharides. Graphical abstract: Image 1 Highlights: Transplanted AR had better efficacy on nephrotic syndrome (NS) than imitation wild AR. Astragalus saponins had better protective effects on MPC5 than astragalus flavonoids. The molecular mechanism of AR treating NS may involve in the metabolism of bilirubin.